2008
DOI: 10.1073/pnas.0804175105
|View full text |Cite
|
Sign up to set email alerts
|

The leaf ionome as a multivariable system to detect a plant's physiological status

Abstract: The contention that quantitative profiles of biomolecules contain information about the physiological state of the organism has motivated a variety of high-throughput molecular profiling experiments. However, unbiased discovery and validation of biomolecular signatures from these experiments remains a challenge. Here we show that the Arabidopsis thaliana (Arabidopsis) leaf ionome, or elemental composition, contains such signatures, and we establish statistical models that connect these multivariable signatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
239
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 280 publications
(257 citation statements)
references
References 30 publications
15
239
0
3
Order By: Relevance
“…Based on the response of frd3 to reduced leaf Fe, we conclude that roots of the TSC10A loss-of-function mutants are also responding to reduced leaf Fe by increasing expression of IRT1. Our conclusion that loss of 3-KDS reductase activity in the TSC10A loss-of-function mutants is causing Fe deficiency is also supported by the observation that Mo accumulation in leaves of the TSC10A loss-of-function mutants is reduced by 67% compared with the wild type, as this is consistent with the reduction in leaf Mo we observed in wild-type plants responding to Fe deficiency (Baxter et al, 2008b). Furthermore, we have previously shown that frd3, a mutant that displays constitutive Fe deficiency responses, also shows a similar reduction in leaf Mo concentration compared with the wild type (Lahner et al, 2003).…”
Section: Discussionsupporting
confidence: 78%
“…Based on the response of frd3 to reduced leaf Fe, we conclude that roots of the TSC10A loss-of-function mutants are also responding to reduced leaf Fe by increasing expression of IRT1. Our conclusion that loss of 3-KDS reductase activity in the TSC10A loss-of-function mutants is causing Fe deficiency is also supported by the observation that Mo accumulation in leaves of the TSC10A loss-of-function mutants is reduced by 67% compared with the wild type, as this is consistent with the reduction in leaf Mo we observed in wild-type plants responding to Fe deficiency (Baxter et al, 2008b). Furthermore, we have previously shown that frd3, a mutant that displays constitutive Fe deficiency responses, also shows a similar reduction in leaf Mo concentration compared with the wild type (Lahner et al, 2003).…”
Section: Discussionsupporting
confidence: 78%
“…4). These results are in agreement with those of [30] who established a multivariate shoot ionomic signature for Arabidopsis, consisting of Mn, Co, Zn, Mo and Cd that is indicative of the nutritional status of plants in relation to Fe. When the Fe supply (via roots) was low, the shoots have enhanced concentrations of Mn, Zn, Co and Cd and less Mo.…”
Section: The Association Of the Root Fc-r With The Concentrations Of supporting
confidence: 82%
“…Conversely, Mn accumulation under Fe deficiency is reduced in 35S-AtNRAMP3 Arabidopsis lines (Thomine et al, 2003). This effect was associated with similar changes in Zn accumulation and other responses to Fe deficiency, suggesting that AtNRAMP3 modulates responses to Fe deficiency (Baxter et al, 2008). In our study, no difference in Mn accumulation was detected between adult wild-type and nramp3nramp4 plants grown under Fe deficiency (Supplemental Fig.…”
Section: Cross Talk Between Fe and Mn Homeostasismentioning
confidence: 47%